Real-time evacuation route selection methodology for complex buildings. (July 2017) - Cuesta, Arturo; Abreu, Orlando; Balboa, Adriana; Alvear, Daniel
Abstract: This paper proposes a novel real-time decision methodology for the selection of optimal evacuation routes for buildings. A summary of the mathematical formulation, the solution algorithm and the computer model are presented. The optimization algorithm is based on the stochastic evacuation model predictions by considering emergency data such as the location of the hazard. The method is applied to an industrial building. The stochastic evacuation model is compared with the commercial evacuation model STEPS. In addition, the computational model is applied to several emergency scenarios to evaluate its validity. Highlights: We propose a real-time methodology for the selection of evacuation routes. The solution optimization algorithm is based on stochastic evacuation model predictions. The computational model is applied to several emergencies to evaluate its validity. The proposed methodology can be used for supporting timely decisions.